Assessing elementary students’ computational thinking in everyday reasoning and robotics programming - Chen, Guanhua; Shen, Ji; Barth-Cohen, Lauren; Jiang, Shiyan; Huang, Xiaoting; Eltoukhy, Moataz (Computers and education, 2017)
Based on a framework of computational thinking (CT) adapted from Computer Science Teacher Association's standards, an instrument was developed to assess fifth grade students' CT. The items were contextualized in two types of CT application (coding in robotics and reasoning of everyday events). The instrument was administered as a pre and post measure in an elementary school where a new humanoid robotics curriculum was adopted by their fifth grade. Results show that the instrument has good psychometric properties and has the potential to reveal student learning challenges and growth in terms of CT. •Assess computational thinking (CT) in ways that are independent of platform.•Assess fifth graders' CT in both everyday and programming settings.•Psychometric analysis of the instrument shows high quality.